SIMBOL DAN AKIDAH ISLAMAnalisis Semiotik terhadap Serat Darmasonya Karya KPH Suryaningrat - Rohmah, Nurul Baiti (Fakultas Ilmu Budaya Universitas Diponegoro, 2015)
Serat Darmasonya written by KPH Suryaningrat was a manuscript using Javanese language and letter, and also in the form of tembang macapat. In its development, Serat Darmasonya was transliterated into the Latin letter and translated into Indonesian language by Suratmin in 1981 and published by Proyek Penerbitan Buku Sastra Indonesia dan Daerah. Transliteration and translation of the manuscript aimed to help the readers especially and the manuscript researchers generally to comprehend its content. Serat Darmasonya contains akidah (beliefs) based on rukun iman in Islam (the five Islam pillars). Islam belief is to believe in the singleness of Allah, the Only One God and the difference between Allah as the Creator and His creatures; the positions, jobs, and form of His angels; the existence of His holy books that are Taurat, Zabur, Injil, and Al-Quran; the prophets as His messengers; the Day of Resurrection; and both good and bad things which happen as His will. The purpose of this study is to reveal the symbols of Islam beliefs contained in Serat Darmasonya. Finding the answer of the research problems, semiotics approach based on Riffaterre’s semiotics theory was used. Basically, this study is a library research. The research data were obtained from the textual sources related to the research object. The result study showed that Serat Darmasonya written by KPH Suryaningrat used the elements of indirection, both as displacing, distorting, and creating meaning. According to heuristics and hermeneutics reading and interpretation, matrics identification, model, variance, and hypogram, it can be concluded that Islam beliefs in Serat Darmasonya manuscript is believing in Allah, His angels, His holy books, His messengers, the Judgement day, and His will (predestination)